2012
DOI: 10.1590/s0102-311x2012000400014
|View full text |Cite
|
Sign up to set email alerts
|

The effects of air pollution on respiratory health in susceptible populations: a multilevel study in Bucaramanga, Colombia

Abstract: We conducted a cohort study to investigate the association between exposure to three different levels of outdoor air pollution and incidence of respiratory symptoms in a population with chronic cardiovascular and respiratory disease. We accompanied 756 participants for a period of six months through the maintenance of a daily record of symptoms and clinic visits. The symptoms with highest incidence rates were sneezing and hacking cough. Multivariate analysis showed that incidence of total symptoms was 60% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Some of the studies that have been conducted in Colombia have evaluated the effect of air pollution on respiratory health with specific population samples [10,11,12]. One such study, which estimated the effect of airborne particulate matter 10 μm or less in diameter (PM 10 ) on mortality at the population level for the city of Bogota, reported that exposure to high levels of PM 10 is associated with an increase in respiratory and cardiovascular mortality, especially for persons from low socio-economic strata [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies that have been conducted in Colombia have evaluated the effect of air pollution on respiratory health with specific population samples [10,11,12]. One such study, which estimated the effect of airborne particulate matter 10 μm or less in diameter (PM 10 ) on mortality at the population level for the city of Bogota, reported that exposure to high levels of PM 10 is associated with an increase in respiratory and cardiovascular mortality, especially for persons from low socio-economic strata [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological evidence sustains a positive association between PM 10 exposure and the increase in cardiovascular diseases (Tonne et al 2012; Pieters et al 2012) and asthma (Delamater, Finley, and Banerjee 2012) on one hand and decrease in gestational age at birth on the other hand (van den Hooven et al 2012). Also, PM 10 exposure is associated with respiratory illness (Rodriguez-Villamizar, Castro-Ortiz, and Rey-Serrano 2012), decrease in lung function (Roy et al 2012), higher blood pressure in children (Sughis et al 2012), increase in hospital admission in aged people (Di Ciaula 2012), and increase in the risk of diabetes complications (Dales et al 2012). The mechanism of cell damage induced by PM 10 exposure has been investigated and the increase in ROS generation is one of the mechanisms involved in its cytotoxicity (Chirino et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Bucaramanga also has an important tradition of studies on air pollution-related adverse effects. The first studies identified respiratory signs and symptoms among susceptible populations [16,17], and the more recent have reported a cluster of cases of childhood cancer, possibly associated with air emissions from an industry in the north of the city [18].…”
Section: Bucaramanga Metropolitan Area (Bma) In Contextmentioning
confidence: 99%